Simulated Thermocline Tilt Over the Tropical Indian Ocean and Its Influence on Future Sea Surface Temperature Variability - Guojian Wang; Wenju Cai; Agus Santoso (Geophysical Research Letters)
Abstract Most coupled climate models simulate an overly shallow thermocline over the southeastern equatorial Indian Ocean (SEIO). Through the Bjerknes feedback loop, the associated unrealistic thermocline tilt leads to warmer sea surface temperature (SST) over the western equatorial Indian Ocean than the SEIO, which is conducive to equatorial easterly winds. Similar to phase 5 of the Coupled Model Intercomparison Project (CMIP), phase 6 of the CMIP continues to simulate such overly tilted thermocline. On the one hand, this leads to overly strong SST variability, and on the other hand, it provides an inherent limit for the thermocline to incline further under greenhouse warming. Consequently, models with a more realistic tilt in the present‐day climate project a greater shoaling of the thermocline under global warming, which facilities upwelling of cool subsurface water, leading to stronger increase in SST variability over the SEIO, compared to models with an overly large thermocline tilt.